A MODERN VIEW ON THE PECULIARITIES OF PROTEIN AND LIPID PEROXIDATION IN ADOLESCENT CHILDREN WITH UNDIFFERENTIATED CONNECTIVE TISSUE DYSPLASIA - Починок, Тетяна; Васюкова, Марина (SWorldJournal, 2026)
The complexity of the morphology, functions and prevalence of connective tissue in the body determine the active participation of its main elements in the formation and development of many types of pathology. According to research conducted by the Departm